Bathymetric Survey Of Urban Water Reservoir: Case Study Of Kathauta Jheel,Lucknow, Uttar Pradesh, India (Prakriti - The International Multidisciplinary Research Journal, 2026)
Conducted within Gomtinagar, Lucknow District, Uttar Pradesh, India, the Bathymetry survey encompassed an approximate area of 2.89 square kilometers. This survey aimed to meticulously gauge water depth, achieving a high degree of accuracy measured in centimeters, while also facilitating a comprehensive three-dimensional perspective. The examination of sediment within the reservoir, vital for urban drinking water supply, was conducted through multiple surveys. Moreover, a dynamic map illustrating water depth at 10-centimeter intervals has been meticulously prepared, covering the entire designated segment.
Keywords: Bathymetry; survey; encompassed; approximate